Analysis of Interaction Network Between Host Protein and M Protein of Swine Acute Diarrhea Syndrome Coronavirus - Xu, Jingya; Cao, Ze; Ji, Chihai; Zhou, Ling; Yan, Xiaoling; Sun, Yuan; Ma, Jingyun (Frontiers in Microbiology, 2022)
Swine acute diarrhea syndrome coronavirus (SADS-CoV) is an enterovirus that can cause acute diarrhea and death in piglets and cause serious economic losses to the pig industry. SADS-CoV membrane (M) protein mainly plays a role in biological processes such as virus assembly, budding and host innate immune regulation. Understanding the interaction between M protein and host proteins is very important to define the molecular mechanism of cells at the protein level and to understand specific cellular physiological pathways. In this study, 289 host proteins interacting with M protein were identified by GST Pull-down combined with liquid chromatography-mass spectrometry (LC-MS/MS), and the protein-protein interaction (PPI) network was established by Gene ontology terms and Kyoto Encyclopedia of Gene and Genomes (KEGG) pathways analysis. Results showed that SADS-CoV M was mainly associated with the host metabolism, signal transduction and innate immunity. The CO-IP validation results of six randomly selected proteins including Rab11b, VDAC1, RPL18, RALY, RHOA and ANXA2 were consistent with LC-MS results. In addition, overexpression of RPL18 and PHOA significantly promoted SADS-CoV replication, while overexpression of RALY antagonized viral replication. This work will help to clarify the function of virus M in the life cycle of SADS-CoV.